The seasons of Arnold's apple tree - Gibbons, Gail. (San Diego : Harcourt Brace, 1984)
As the seasons pass, Arnold enjoys a variety of activities as a result of his apple tree. Includes a recipe for apple pie and a description of how an apple cider press works.
Book Links (A.L.A.).
School Library Journal.
Wilson's Children.
2.5.
2.5
K-3
Keywords: Apples -- Fiction; Seasons -- Fiction; Apples -- Fiction; Seasons -- Fiction